A genre-based approach in the secondary school English writing class: Voices from student-teachers in the teaching practicum - Liu, Chang; Chen, Meihua (Frontiers in Psychology, 2022)
While the genre-based approach (GBA) has assumed increasing prominence in discussions of writing pedagogy for diverse classrooms, little is known about how secondary school student-teachers understand and adopt genre pedagogies in the English as a foreign language (EFL) writing class. Based on the data from semi-structured interviews and teaching materials, this study examined Chinese EFL student-teachers’ knowledge and use of genre-based writing instruction (GBWI) during the teaching practicum and explored the challenges they encountered in enacting it. The findings demonstrated that teacher informants showed some familiarity with genre pedagogies, especially in terms of scaffolding the linguistic features and semantic patterns in the focused genres. However, they were generally confused over the connection between language, content, and context, and their GBWI practice scarcely involved the explicit teaching of the linguistic and semantic choices for a specific audience and context, which gave rise to some perceived tensions in the teaching reality. Further probing has revealed the complex interplay between Chinese EFL student-teachers’ professional knowledge, perceived difficulties and genre instructional practice in the secondary school writing class. The study concludes with practical implications for the student-teachers’ professional development of effective GBA.